"Master Teacher" Transformative Learning Strategy in Digital Media: "Ruangguru" in Indonesia - Jenny Ratna Suminar; Ditha Prasanti; Sarah Aisha (MO.RI Publishing, 2022)
Ruangguru is a digital media learning application created by a startup that understands Generation Z. It provides teaching materials for elementary, junior high, and high school children that can be accessed via Android, iOS, and PC (Windows and macOS), as part of their daily use. This breakthrough was made to maintain school-aged children's interest and motivation to learn, as Ruangguru carries the tagline: Belajar Jadi Luar Biasa (Learning Becomes Extraordinary) through facilities such as videos, practice exercises, private lessons, as well as tryouts. The novelty in this study lies in the concept of "Master Teacher". Based on the observation and interviews conducted, Ruangguru uses the term "Master Teacher" to refer to the instructors, which raises an understanding of the quality instructors Ruangguru has. Therefore, the researchers intend to reveal the Master Teacher's learning strategy during the online learning process through digital media. The objectives of this study are as follows: 1) to explore the Master Teacher's learning strategy while preparing interesting digital media-based applications; 2) to identify Ruangguru's target audience 3) to explore reasons for using Master Teacher as part of the learning strategy. The research has used case study as a qualitative method to collect data through interviews, observation, and literature studies. The results of this study indicate that: 1) Ruangguru as a learning application provides content for various levels in an interesting way through videos, practice questions, private lessons, tryouts which can be accessed from a smartphone; 2) Ruangguru's content is adapted from the national curriculum and specifically designed by the best and experienced teachers. It is aimed at Generation Z ranging from elementary, junior high, to high school students; 3) Master Teacher (MT), as Ruangguru's strong point, serves as a representative in delivering digital media-based transformative learning strategies to Generation Z; 4) Transformative learning strategy is used by Ruangguru Master Teacher (MT) because it suits Generation Z's characteristics that like Ruangguru's digital media as a platform to deliver messages. Since the urgency and potential of learning through digital media are considered as an important finding in this research, it is recommended that the results of this study are utilized, disseminated, and developed in learning processes.